2019
DOI: 10.1016/j.heliyon.2019.e02265
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic measures of gamma oscillations

Abstract: Background: Gamma oscillations serve complex processes, and the first stage of their generation is the reticular activating system (RAS), which mediates the gamma-activity states of waking and paradoxical sleep. We studied whether the pedunculopontine nucleus (PPN), part of the RAS in which every cell manifests intrinsic gamma oscillations, undergoes changes resulting in distinctive protein expression. New method: We previously found that a histone deacetylation inhibitor, trichostatin A (TSA), acutely (30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…We previously described proteomic analysis following in vitro preincubation with CAR or CAR ϩ TSA (2). We observed significant changes particularly in several proteins related to F-actin cytoskeleton and intracellular [Ca 2ϩ ] regulation in the PPN (2). Other authors have also described fast actions of the HDAC inhibitors SAHA and MS275 on the acetylation of several proteins related to the cytoskeleton (5).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…We previously described proteomic analysis following in vitro preincubation with CAR or CAR ϩ TSA (2). We observed significant changes particularly in several proteins related to F-actin cytoskeleton and intracellular [Ca 2ϩ ] regulation in the PPN (2). Other authors have also described fast actions of the HDAC inhibitors SAHA and MS275 on the acetylation of several proteins related to the cytoskeleton (5).…”
Section: Discussionsupporting
confidence: 63%
“…The recent results of our group showed that 1) acute in vitro exposure to the histone deacetylation inhibitor trichostatin A (TSA) led to lower activation of high threshold, voltage-dependent Ca 2ϩ channel-mediated intrinsic membrane oscillations, specifically in the gamma-band range, but not lower frequency oscillations; 2) preincubation with TSA led to a similar decrease specifically in gamma-band oscillations; and 3) a significant reduction in calcium currents was elicited by TSA (11,34). These changes in PPN rhythmicity could be explained by decreased deacetylation of histones (i.e., changes in gene expression) and/or changes in the deacetylation of other protein targets like CaMKII and F-actin (2,5). Indeed, proteomic analysis of PPN tissue samples after preincubation (30 -60 min, in vitro) with carbachol (CAR) or CAR ϩ TSA showed significant protein changes related to F-actin cytoskeleton and intracellular Ca 2ϩ concentration ([Ca 2ϩ ]) regulation (2).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations